Contrast-enhanced ultrasound microbubble uptake and abnormal plasma biomarkers are seen in patients with abdominal aortic aneurysms - Adham N. Abou Ali, MD; Patrick Cherfan, MD; Ashraf G. Taha, MD; Michel S. Makaroun, MD; Yingze Zhang, PhD; Xucai X. Chen, PhD; Flordeliza S. Villanueva, MD; Rabih A. Chaer, MD (JVS - Vascular Science)
Objective: Abdominal aortic aneurysm (AAA) growth is unpredictable. We hypothesize that contrast-enhanced ultrasound (CEUS) imaging and plasma inflammatory biomarkers (PIBs) may detect AAA wall inflammation. Methods: Patients with an AAA diameter ≥4 cm had CEUS and PIB testing at enrollment and every 6 months. Microbubble replenishment was analyzed via manually drawn regions of the aortic wall. Aneurysm growth, rupture, and repair were recorded. PIB testing was analyzed using biomarker panels. Independent and paired t-tests were used to detect differences in PIB levels. Logistic regression was used to study the association between PIBs, microbubble uptake, and AAA growth. Results: A total of 59 patients were enrolled (mean age, 68.8 ± 8.6 years; 13.6% female; 93.2% White). Mean AAA size on presentation was 41.6 ± 6.7 mm. Microbubble uptake was seen in 36 patients (61%). Patients with AAA had high baseline levels of Cystatin C and interferon-γ and low levels of macrophage migration inhibitory factor. Microbubble uptake was seen in 59% of patients with ≥5 mm AAA growth but was not predictive of growth on logistic regression. Conclusions: We have demonstrated that microbubble uptake with CEUS is seen in the aortic wall/intraluminal thrombus of patients with AAA. CEUS and PIBs could provide insight into aneurysm behavior in newly diagnosed AAA. : Clinical Relevance: Microbubble contrast agents hold significant clinical relevance for the evaluation of aneurysms, offering an innovative approach to enhancing diagnostic imaging and improving patient outcomes. These agents, when used in ultrasound or other imaging modalities, allow for the detailed visualization of tissue characteristics within the aneurysm wall. By enhancing the contrast between the aneurysm and surrounding tissues, microbubbles provide a more precise assessment of wall integrity and vascularization by assessing the vasa vasorum density. This improved visualization can be crucial for identifying aneurysms that are at higher risk of rupture, enabling timely interventions such as surgical repair or endovascular procedures. Additionally, microbubble contrast can help in monitoring the effectiveness of treatments or interventions over time, offering a non-invasive, repeatable method for tracking aneurysm progression and endoleak detection. Ultimately, the use of microbubble contrast in aneurysm evaluation could lead to more personalized treatment strategies, reducing the risk of rupture and improving patient prognosis through better-informed decision-making.